Do symptoms arise from hyperlipidemia due to hyperviscosity or through its atherosclerotic consequences? – A case series exploration - Amit Chakraborty; Subhadip Basak; Sudipan Mitra; Amit Sarkar; Shubham Kumar; Smarajit Banik (Asian Journal of Medical Sciences)
Hyperlipidemia does not cause any symptoms itself. Hypercholesterolemia contributes to atherosclerotic plaques inside arteries and obstruction of arteries, producing clinical manifestations. Very severe hypertriglyceridemia can cause acute pancreatitis. The three patients with hyperlipidemia in the present study had complaints of chest pain, breathlessness, limb aches, tingling sensations, and sleepiness without any evidence of atherosclerosis. The possible explanation of the visible symptoms in the patients can be due to a mild increase in blood viscosity due to hyperlipidemia. However, further intensive studies may be required to comprehend the direct symptoms of hyperlipidemia towards early detection and intervention to reduce the burden on healthcare facilities.